2019
DOI: 10.3389/fimmu.2019.01951
|View full text |Cite
|
Sign up to set email alerts
|

Accelerated and Severe Lupus Nephritis Benefits From M1, an Active Metabolite of Ginsenoside, by Regulating NLRP3 Inflammasome and T Cell Functions in Mice

Abstract: Chinese herbal medicines used in combination have long-term been shown to be mild remedies with “integrated effects.” However, our study provides the first demonstration that M1, an active metabolite of ginsenoside, exerted its dramatic therapeutic effects on accelerated and severe lupus nephritis (ASLN) mice, featuring acute renal function impairment, heavy proteinuria, high serum levels of anti-dsDNA, and high-grade, diffuse proliferative renal lesions. In the present study, NZB/WF1 mice were given injection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 61 publications
0
28
0
Order By: Relevance
“…The positive outcomes were showcased by inhibiting NF-κB-associated priming, and by modulating STAT3 signaling and NLRP3 inflammasome activation ( Table 4 ) [ 112 ]. Likewise, another study showed the protecting effects of CK on accelerated and severe lupus nephritis by hindering activation of NLRP3 inflammasome [ 113 ]. Ren and coworkers evaluated the protecting effects of CK and its analogues against asthma.…”
Section: Health-promoting Activitiesmentioning
confidence: 99%
“…The positive outcomes were showcased by inhibiting NF-κB-associated priming, and by modulating STAT3 signaling and NLRP3 inflammasome activation ( Table 4 ) [ 112 ]. Likewise, another study showed the protecting effects of CK on accelerated and severe lupus nephritis by hindering activation of NLRP3 inflammasome [ 113 ]. Ren and coworkers evaluated the protecting effects of CK and its analogues against asthma.…”
Section: Health-promoting Activitiesmentioning
confidence: 99%
“…CK inhibited the IgE/antigen-complex-induced cell degranulation in RBL-2H3 cells and oxazolone-induced chronic dermatitis in mice [36]. Lin et al reported that CK improved the accelerated and severe lupus nephritis in mice by blunting NLRP3 inflammasome activation and regulating T cell functions [85]. CK and its derivatives inhibited IgE production in mice with ovalbumin-sensitized asthma [86].…”
Section: Anti-allergic Effects Of Ginseng Constituentsmentioning
confidence: 99%
“…The NLRP3 in ammasome has been proven to participate in immune rejection post-transplantation in graftversus-host disease (GVHD), as well as heart, kidney, and skin transplantations [11,12]. Studies have shown that the NLRP3 in ammasome is associated with the M1 polarization of macrophages [13].…”
Section: Introductionmentioning
confidence: 99%